Almacén inteligente mediante robot omnidireccional y visión artificial. - Calvopiña Limaico, Zaira Belén (2018)
In this titling work, the development of an intelligent warehouse using an omnidirectional robot and artificial vision is presented. The Robotino of the FESTO brand is used, which will be responsible for storing and dispatching products, by controlling an axis of freedom in "z" implemented in the robot with its gripper clamp. The Raspberry Pi 3 data acquisition card is used to capture, detect and decode QR codes, as well as control the storage and dispatch system. Python is used for the development of control algorithms for reading and interpretation of QR codes, these are responsible for informing the robot the name of the product and the position in which each must be located both in storage and in the office. The development of control algorithms for the movement of the movable axis in "z" and the gripper clamp was also carried out. An interface is developed, which shows the state, empty or full, of the locations in the three-dimensional warehouse. For the movement of the robot in the work area, Labview 2015 is used with its specific control libraries for Robotino. The displacement of the robot is implemented by means of a line follower algorithm, allowing the robot to move in a guided manner towards each of the locations of the warehouse. Finally it should be noted that the entire system implemented in the robot is completely autonomous.